Acute and Subacute Toxicity Assessment of Oxyclozanide in Wistar Rats - Wang, Weiwei; Dong, Zhen; Zhang, Jili; Zhou, Xuzheng; Wei, Xiaojuan; Cheng, Fusheng; Li, Bing; Zhang, Jiyu (Frontiers in Veterinary Science, 2019)
Oxyclozanide is an effective anthelmintic and has shown good properties in other ways including anti-adenovirus, anti-biofilm, antifungal and antibacterial activity. This study aimed to investigate the acute and subacute 28-day repeated dose oral toxicity of an oxyclozanide suspension in Wistar rats. A high oral lethal dose (LD50) of 3707 mg/kg was observed in the acute toxicity test. During the 28-day time period, no obvious adverse effects or death were detected. Histopathological changes were observed in the heart, liver, kidney of animals treated with high-dose of oxyclozanide. Based on the haematological parameters, there were no statistical differences between oxyclozanide treated group and control group. For biochemistry assays, ALP, AST, GLU, TBIL, GLO, TG, BUN, UA, LDH, CK were statistically changed in the treatment groups. These data suggested that the LD50 of oxyclozanide was approximately 3707 mg/kg. body weight (BW), and the lowest observed adverse effect level (LOAEL) of oxyclozanide was at a dose of 74 mg/kg in rats.